1980
DOI: 10.1038/ki.1980.114
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary calcification in hemodialyzed patients detected by technetium-99m diphosphonate scanning

Abstract: Metastatic pulmonary calcification, a well-known complication in patients with chronic disease, has been demonstrated postmortem in patients with a negative chest X-ray. Recently, scintigrams with bone-seeking radionuclides have been used to detect such subclinical pulmonary calcium deposits. We describe 23 patients on maintenance hemodialysis with no evidence of pulmonary calcification on chest X-ray who were prospectively studied by lung scanning with a bone-seeking radionuclide and pulmonary function testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 17 publications
2
43
0
Order By: Relevance
“…Tissue calcification is a well-known complication in patients with chronic renal disease [1][2][3], but rarely radiographic evidence of its presence is provided [9], and it usually occurs after a long period of HD [4], However, our case developed extensive metastatic calcifications of lung, bones, vessels, skin, uterus and other soft tissue after only 3 months of maintenance HD.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Tissue calcification is a well-known complication in patients with chronic renal disease [1][2][3], but rarely radiographic evidence of its presence is provided [9], and it usually occurs after a long period of HD [4], However, our case developed extensive metastatic calcifications of lung, bones, vessels, skin, uterus and other soft tissue after only 3 months of maintenance HD.…”
Section: Discussionmentioning
confidence: 81%
“…Before HD pH was 7.351, pC 02 29. 4 Before initiation of HD, she has never received aluminum salts for treatment of gastrointestinal symptoms or controlling scrum phosphate levels, although calcium carbonate and alfacalcidol were intermittently given.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…High serum PTH induces osteitis fibrosa and bone loss, thus increasing serum Ca ϫ P product (29,30) and ectopic calcification (3,31). In addition to the described effects regarding bone resorption, high PTH may also cause metastatic microcalcifications through elevations in cytosolic Ca (9,10). In rats, Borle et al (16) showed that high P-induced hyperparathyroidism caused nephrocalcinosis.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated PTH levels cause ectopic calcification not only by enhancing serum P and Ca ϫ P product through inducing high bone turnover, but also by increasing both serum and intracellular calcium (Ca) (9 -10). The control of serum P in patients with chronic renal failure is therefore important to the prevention of increases in Ca ϫ P product, secondary hyperparathyroidism, and ectopic calcifications (9).…”
mentioning
confidence: 99%